Students perceptions on formative assessment: differences between groups at the beginning and at the end of degree - David Hortigüela Alcalá; Víctor Abella García; Ángel Pérez Pueyo (Universitat Politècnica de València, 2015)
In this paper the results on the perception of the students on formative assessment processes carried out in the university are presented, focusing on understanding the system and monitoring conducted throughout the course in relation to this work students enrolled subjects, first, 1st and 2nd year and, second, 3rd and 4th. The sample used is 3460 students, corresponding to 51 subjects of 17 Spanish universities; in all were conducted formative evaluation processes. The students were divided in 2 groups, one called "initial training" (1764 students) and one called "final course" (1696 students). We used a validated questionnaire on evaluation methodology and initial training, in which different items related to formative assessment specified. It has employed a quantitative analysis, divided into descriptive: frequencies and percentages and inferential: contingency tables and χ2 and ANOVA, using this latter technique based on the positive perception of the assessment based on learning processes items and the number of times the student is enrolled in courses. The findings of this research show: a) formative assessment systems are perceived positively by students; b) the quality of the tasks required increases, recognizing that greater involvement is needed for work and an understanding of the system from the beginning does not build; c) the number of times the student is enrolled in the course not directly affects their perception of this type of process.